The Influence Of E-Money And Prestige On The Consumptive Behavior Of Generation Z In Muara Sabak Barat - Khairul Zikri; M.Arif Musthofa2; Daud Daud; Erwina Kartika Devi (Journal of Innovative and Creativity, 2025)
Click here and insert abstract your text. Insert an abstract of 200-300 words, giving a brief account of the most relevant aspects of the paper. The study purpose was to analyze the influence of e-money usage (X1) and prestige (X2) on consumptive behavior (Y) among Muslim Generation Z in Muara Sabak Barat District. With the rapid development of financial technology and the strong drive for social status, Generation Z—as digital natives—is particularly vulnerable to impulsive and unplanned consumption patterns. This study seeks to explore how the ease of digital financial services and the psychological need for social recognition jointly shape their consumer behavior. Materials and methods. This research employed a quantitative approach. Questionnaires were distributed to 95 respondents selected through stratified random sampling and purposive sampling techniques, from a total population of 6,233 Muslim individuals aged 13–28 years. Inclusion criteria included basic understanding of digital financial services and permanent residence in the research area. The data were analyzed using multiple linear regression with the aid of SPSS software. Results. Findings revealed that e-money and prestige simultaneously have a significant effect on consumptive behavior, as indicated by an F-value of 8.897 and a significance level of 0.000 (< 0.05). Partially, e-money shows a significant influence (Sig. = 0.039), as does prestige (Sig. = 0.009). The coefficient of determination (R²) was 0.162, indicating that 16.2% of the variation in consumptive behavior is explained by the model, while 83.8% is attributed to other variables. Conclusions. The study concludes that both digital transaction convenience and social image motivation significantly contribute to consumptive behavior among Muslim Generation Z. However, other factors such as financial literacy, self-control, and social media influence may also play a critical role and deserve further investigation in future research.